Taxonomic and nomenclatural notes on the Rhinusa tetra (Fabricius) species complex (Coleoptera: Curculionidae) - Caldara, Roberto; Casalini, Roberto; Baviera, Cosimo (Zootaxa, 2012)
All taxa closely related to or synonymized with Rhinusa tetra (Fabricius, 1792) are studied, including the available type mate-rial. Four species are considered taxonomically valid: Rhinusa tetra, R. comosa (Rosenschoeld, 1838), R. moroderi (Reitter,1906), R. verbasci (Rosenschoeld, 1838). The following four new synonymies are proposed: R. tetra (= Gymnetron eoumRosenschoeld, 1838 syn. n.; = Cleopus uncinatus Dufour, 1843 syn. n.; = Cleopus verbasci Dufour, 1843 syn. n.); R. moroderi(= Gymnetron otini Hustache, 1946 syn. n). Neotypes are designated for Cionus amictus Germar, 1821, Cleopus uncinatus andCleopus verbasci. Lectotypes are designated for Curculio teter, Gymnetron comosum, Gymnetron crassirostre Lucas, 1849,Gymnetron eoum, Gymnetron fuscescens Rosenschoeld, 1838, Gymnetron haemorrhoum Rosenhauer, 1847, Gymnetron moro-deri, Gymnetron plagiellum Gyllenhal, 1838, Gymnetron trigonale Gyllenhal, 1838 and Gymnetron verbasci, all currentlyincluded in Rhinusa. A key separating the four valid species is supported by diagnoses, biological notes, distributional data andillustrations. These new findings are important because R. tetra in the broad sense was proposed as a potential candidate for the biological control of invasive Common Mullein (Verbascum thapsus L.) in North America.